Exploring the potential of Mathematics; Innovative Mobile Application for multiplication by 5, Sharpening Students' Critical Thinking and Mathematical Computational Skills - Khoerul Umam; Abdul Hakim Ma'ruf; Ervin Azhar; Hari Setiadi (Journal of Instructional Mathematics, 2025)
The integration of innovative digital tools offers a promising avenue to address traditional learning hurdles and enhance student engagement. This study aims to develop a mobile application to improve students' critical thinking and mathematical computational skills in the material of the multiplication rule of 5. The low level of both abilities and the limitations of innovative learning media. The use of the ADDIE development research method. The results of the study showed that the application was significantly successful in improving computational skills and critical thinking skills, which was empirically proven by increased test scores and active student involvement during the mathematics learning process. An important contribution in providing effective digital learning solutions for basic materials as a foundation in developing knowledge for students. Furthermore, this application serve as a scalable model for integrating technology to address fundamental learning gaps in mathematics across various educational settings. Its success suggests the potential for broader adoption of similar tools to foster essential cognitive skills from an early age.